Investigation on soil thermal saturation and recovery of an earth to air heat exchanger under different operation strategies. (25th February 2015) - Niu, Fuxin; Yu, Yuebin; Yu, Daihong; Li, Haorong
Abstract: A great portion of the primary energy is consumed by space heating and cooling in buildings. The need for utilizing more renewable energy in the building sector remains critical for ensuring the energy and environment sustainability. Geothermal energy is one of the renewable energy sources that we have an easy access to for supplying low grade thermal energy with a low impact on the environment. The methods of utilizing geothermal energy for buildings include such as ground source heat pumps and earth to air heat exchangers (EAHEs). Understanding the thermal saturation and recovery of soil around the heat exchangers is of great importance to ensure the successful and efficient use of a geothermal energy based system. This study addresses two dimensional dynamic heat transfer mechanism of EAHE through a transient control volume method. The soil computing domain is divided into control units along the axial and radius directions. A thermal balance of each unit is built to calculate the whole soil domain temperature based on a sequential method. The numerical result is validated by testing data based on an existing experimental facility. In order to analyze the self-recovery ability during the nonworking time, the performance of EAHE under both continuous and intermittent operation conditions is discussed. The research suggests that the soil temperature and the cooling capacity can recover during the nonworking time in an intermittent operation mode. The recovery capability of soil gradually reduces along the axial of the tube away from the inlet with the soil temperature increasing. The supply air temperature and the cooling capacity in the intermittent operation mode are more powerful than that of continuous operation mode. The research can be utilized for the design and operation management of EAHE. Highlights: We investigated the soil saturation and recovery of an EAHE. The model is constructed with numerical transient control volume method. The numerical result is validated by testing data from an experimental facility. The soil has recovery capability in the intermittent operation mode. The cooling capacity is higher with low temperature in the intermittent operation.